Management of the Information System for Poverty Alleviation at the Lampung Provinsial Regional Development Planning Agency - Mapala, Yurisman; Kagungan, Dian; Sulistio, Eko Budi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
This study discusses the management of the Poverty Alleviation Management Information System (SIMNANGKIS) at the Regional Development Planning Agency (BAPPEDA) of Lampung Province, with a qualitative descriptive approach. The purpose of the study is to explain the stages of planning, organizing, implementing, and supervising in the management of SIMNANGKIS. Data were obtained through interviews, observations, and documentation. The results of the study show that the planning of SIMNANGKIS in BAPPEDA Lampung Province includes socialization and budget determination, but is constrained by the lack of skilled human resources and data updates are not carried out on the SIMNANGKIS application.  Organizing is colored by challenges in coordination and suboptimal division of tasks. At the implementation stage, the SIMNANGKIS application has run well according to procedures, but there are weaknesses in the latest data input. Supervision of SIMNANGKIS involves determining implementation standards and evaluations, but is constrained by a lack of coordination between SIMNANGKIS operators and the Communication and Informatics Office. In conclusion, although management functions have been implemented, there are several obstacles that need to be overcome, including more specific budget planning, improved coordination between organizational units, and data updates within the application. With improvements in these aspects, BAPPEDA Lampung Province is expected to be able to more effectively manage SIMNANGKIS and achieve poverty alleviation goals in the province.